The Role of Organizational Strength in Promoting Entrepreneurial Orientation: An Analytical Study of the Opinions of College Council Members in a Sample of Private Universities in Erbil, Kurdistan Region of Iraq. - إبراهيم ولي احلام; خلف ئارمان (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The research aims to determine the relationship and impact of organizational power in private universities, which is represented by their dimensions (solid power, flexible power), in the dimensions of the pioneering orientation of (orientation towards creativity, orientation towards risk tolerance, pro activeness). The general framework for research is the research problem, which has been identified by raising several questions about the nature of the relationship and the impact between the independent variable (organizational power) The variable adopted (entrepreneurial orientation) was designed, and for this reason, a hypothetical scheme was designed that produced a set of key hypotheses, and in order to ascertain the validity of the hypotheses, all of which were subject to multiple tests, the resolution form was used as a key tool for obtaining data. The research adopted the descriptive analytical approach, describing the main and sub-variables, as well as analysing the relationships and impact between the variables, representing the research community of all the 9 private universities in Erbil, Kurdistan, Iraq. The sample consisted of 7 universities, while the 79 responding individuals were members of college boardsIn the selected sample of universities. Hypotheses were tested through a set of statistical tests by software (SPSS V.23). The research reached a set of conclusions, the most important of which is the existence of positive correlations and strong effects between the main and sub-variables, at the macro and partial level. The research suggested a range of proposals, including the need to harness strong relationships between the two variables and their orientation towards serving researched universities.